Association of Cutibacterium acnes with human thyroid cancer - Trivedi, Vaishakhi; Noronha, Vanita; Sreekanthreddy, Peddagangannagari; Desai, Sanket; Poojary, Disha; Varghese, Linu; Gowda, Pooja; Butle, Ashwin; Mishra, Rohit; Bal, Munita; Mittal, Neha; Rane, Swapnil; et al. (Frontiers in Endocrinology, 2023)
The diverse subtypes of thyroid carcinoma have distinct clinical outcomes despite a comparable spectrum of underlying genetic alterations. Beyond genetic alterations, sparse efforts have been made to characterize the microbes associated with thyroid cancer. In this study, we examine the microbial profile of thyroid cancer.We sequenced the whole transcriptome of 70 thyroid cancers (40 papillary and 30 anaplastic). Using Infectious Pathogen Detector IPD 2.0, we analyzed the relative abundance of 1060 microbes across 70 tumors from patients with thyroid cancer against 118 tumor samples from patients with breast, cervical, colorectal, and tongue cancer.Results: Our analysis reveals a significant prevalence of Cutibacterium acnes in 58.6% thyroid cancer samples compared to other cancer types (p=0.00038). Immune cell fraction analysis between thyroid cancer samples with high and low Cutibacterium loads identify enrichment of immunosuppressive cells, including Tregs (p=0.015), and other anti-inflammatory cytokines in the tumor microenvironment, suggesting an immune evasion/immunosuppression milieu is associated with the infection. A higher burden of Cutibacterium acnes was also found to be associated with poor survival defining a distinct sub-group of thyroid cancer.Cutibacterium acnes is associated with immune suppression and poor prognosis in a subpopulation of thyroid cancer. This study may help design novel therapeutic measures involving appropriate antibiotics to manage the disease better.